An analysis of the ERP Implementation on the Effectiveness of Maintenance of Production Facilities in oibl ltd - Sukaria Sinulingga; Rahim Matondang; S Bafzal (Industrial Engineering Journal, 2017)
Business environtment today is more global and competitive for medium and big companies; therefore, Enterprise Resource Planning is commonly used. Enterprise Resouce Planning, which is an integrated package application software and used widely in organizations that support automation throughout the process of business and industry, also affects the operation of management. Ophir Indonesia Bengkanai Limited (OIBL) is an oil and gas company which is focused on exploration and production. iIn running their business, OIBL uses the Workmate as data base for its Enterprise Resource Planning. One of the functions of the workmate is the maintenance module which is used for running the Computerized Maintenance Management System (CMMS). ERP implementations remain problematic despite the fact that many of the issues are by now quite well known. The type of this research was correlation investigations. The population was about 85 employees of Ophir Energy Indonesia, and 50 of them were used as the samples. The research location was in the field and Jakarta Office. The data were gathered by distributing questionnaires and analyzed by using multiple regression analysis which consisted of F-test simulateneous F-tes and partial T-test. The result of the research showed that the key users and management of change had significant influence on the effectiveness of the implementation of ERP program in the company. It is suggested that Ophir Energy Indonesia Bangkanai Ltd increase the competency of the employees (key users) by providing appropriate training so that the ERP implementations can run successfully.